2011
DOI: 10.1002/qua.23145
|View full text |Cite
|
Sign up to set email alerts
|

DFT studies of homogeneous catalysis in the gas phase: Dehydration kinetics of several tertiary alcohols with hydrogen chloride

Abstract: ABSTRACT:The mechanisms for the acid-catalyzed gas-phase dehydration of the tertiary alcohols 2-methyl-2-propanol, 2-methyl-2-butanol, and 2-methyl-2-pentanol were examined at B3LYP/6-31G(d), B3LYP/6-31G(d,p), B3LYP/6-31G(2d,p), B3LYP/6-31G(2d,2p), /6-31G(2d,p), and MPW91PW91/6-31G(2d,2p) levels of theory. Calculation results suggest that the dehydration processes catalyzed by hydrogen chloride to give the corresponding olefin and water occur with the formation of Van der Waals complexes between the alcohol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Several kinetic investigations have indicated that the formation of ethers through an Ad E 2 mechanism and subsequent ether‐splitting could provide an alternative pathway 19. 20 For the hydrochloric acid‐catalyzed gas phase dehydration, a concerted six‐membered transition‐state has been proposed on the basis of DFT calculations, with the HCl proton linked to the OH group and the chloride linked to the hydrogen atom at the β‐position 21. In the case of alcohol dehydration over γ‐alumina, the mechanism seems different from that of simple Brønsted acids, as the involvement of free carbenium ions, as in the E1 mechanism, can be ruled out on the basis of kinetic isotope effect (KIE) studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several kinetic investigations have indicated that the formation of ethers through an Ad E 2 mechanism and subsequent ether‐splitting could provide an alternative pathway 19. 20 For the hydrochloric acid‐catalyzed gas phase dehydration, a concerted six‐membered transition‐state has been proposed on the basis of DFT calculations, with the HCl proton linked to the OH group and the chloride linked to the hydrogen atom at the β‐position 21. In the case of alcohol dehydration over γ‐alumina, the mechanism seems different from that of simple Brønsted acids, as the involvement of free carbenium ions, as in the E1 mechanism, can be ruled out on the basis of kinetic isotope effect (KIE) studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Julio et al studied the gas‐phase elimination kinetics of aliphatic unsaturated aldehydes in the presence of hydrogen chloride, showing that the reaction occurs in a homogeneous and molecular manner [8]. Moreover, Mora and coworkers have evaluated the dehydration kinetics of several tertiary alcohols using hydrogen chloride as catalyst [9]. Their results showed that this reaction is molecular in nature and occurs through a six‐membered transition state.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing different functional groups the following reactivity was found acid<ester<alco-hol<ether (Stimson & Tilley, 1972). In 2012, Mora et al studied the hydrogen chloride catalyzed dehydration reaction mechanism of several tertiary alcohols (Jose R. Mora et al, 2012); while, in 2015, Julio et al worked on elucidating the gas phase elimination kinetics of aliphatic unsaturated aldehydes catalyzed by hydrogen chloride (Julio, Mora, Maldonado, & Chuchani, 2015). Their results suggest these reactions are homogeneous and unimolecular.…”
Section: Introductionmentioning
confidence: 99%